Tradisi Ganjuran Di Desa Ngambeg Kecamatan Pucuk Kabupaten Lamongan (Teori Folklor) - Vina Tri Agustinningrum; Sukarman Sukarman (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research conducted on the ganjuran ds ngambeg tradition in Puncak, Lamongan Regency, namely to find out and explain clearly. The research uses folklore theory, namely the concept of Danandjaja. The method used in the research is descriptive qualitative with interview, observation and documentation techniques. The research instrument is a researcher, a list of questions and an observation sheet. The aim of this research is 1) to explain the origins of the ganjuran tradition in Ngambeg village, Puncak district, Lamongan district. 2) Explain the procedures for the Ganjuran tradition. 3) Explain the ubarampe and its meaning in the Ganjuran tradition. 4) Explain the benefits or uses of the ganjuran tradition. 5) Explain how to preserve the ganjuran tradition. The results of research on the ganjuran tradition in Ngambeg Village can be seen that the origins of Ngambeg Village are from Panji Laras and Panji Liris which are loved by Dewi Andanwangi and Dewi Andansari. The procedures for this tradition consist of the preparation and closing stages. Ubarampe from the ganjuran tradition is 1) Sugar and Coffee 2) tetel 3) lemet 4) Wingko 5) Krecek 6) Sticky Rice Salak 7) Side dishes 8) Bananas 9) Bongko 10) Bread 11) Kalender. The uses of the Ganjuran tradition are 1) as a projection system 2) as a system of rules for cultural institutions 3) as a tool for education 4) as a tool for monitoring society, then other uses are 1) for economic activities 2) religious or religious 3) social. The way to preserve the ganjuran tradition is by passing it down from generation to generation and utilizing social media.